Po sledeh jezikovnih travm v sodobni slovenski književnosti - Paternu, Boris (Jezik in slovstvo, 2005)
Linguistic trauma is a frequent topics of contemporary Slovene literature. It is most notable when it concerns the question of a writer's personal choice between Slovene language and a foreign language. The linguistic distress of older writers, eho in their youth had to survive the linguistic genocide of Fascism and Nazism, is demostrated in the sign o great stress and trauma. At the time of democracy and globalisation, younger authors seem to demonstrate a phenomenon which is quite the opposite: opting freely for a foreign language, withdrawing from Slovene. In both cases of linguistic exposure, that of the genocide and that of globalisation, the writer's linguistic sense is exposed to depression and stress. Typical of this is that trauma caused by genocide can trigger off an increasing linguistic and stylistic creativity of the endangered language. This is illustrated through examples bythe writers Florjan Lipuš, Lojze Kovačič and Brina Svit.
Keywords: Lipuš, Florjan, 1937-; Kovačič, Lojze, 1928-2004; Švigelj-Mérat, Brina, 1954-; Slovene literature; slovenska književnost; slovenščina; Slovene; materinščina; first language; tuji jeziki; jezikovna zavest